Aussprachenormen für das Sprechen und Singen auf der Bühne im 19. Jahrhundert - Hoffmann, Ulrich Thilo (Frank & Timme, 2024)
The development of oral language norms prior to the publication of Theodor Siebs' set of rules "Deutsche Bühnenausprache" (1898) has hardly been systematically studied to date. Ulrich Thilo Hoffmann offers the first comprehensive overview of recognized and controversial pronunciation norms in the 19th century. His analysis of the stage-adequate pronunciation of vowels and diphthongs in the historical specialist literature includes Konrad Duden, Jacob and Wilhelm Grimm, Julius Hey and Wilhelm Viëtor as well as numerous lesser-known authors. Hoffmann thus makes a linguistic contribution to the debate on the development of the German standard language. At the same time, his book is a research impulse for musicology, specifically for the examination of vocal pronunciation in historically informed performance practice. The results of the study are already being used in the projects Wagner-Lesarten and The Wagner Cycles, which are pursuing the historically informed performance of Richard Wagner's Ring des Nibelungen under the direction of Kent Nagano.